Peran Guru PAI dalam Meningkatkan Disiplin Ibadah Shalat Siswa SMAN 2 Kota Bekasi - Widianto .; Wisnawati Loeis (Turats, 2015)
This study was to determine the role of teachers Islamic education (PAI) in improving discipline in students prayers. This study used a qualitative approach. Indicators of the success of the process of improving the discipline of praying students on the subjects of Islamic education (PAI) in SMA 2 Kota Bekasi are students implemented to carry out obligatory prayers in congregation and duha prayer (shalat duha) at home while being off from school because it was used to implement obligatory prayers in congregation and duha prayer in school. In addition, students have understood the primacy of obligatory prayers on time and in congregation. Another success is the students more wisely used the time to worship of the activities that are not useful, than all the success factors is a contributing factor in improving the discipline of praying students is the teacher's role of Islamic education already provide examples of behavior and apparent, provide motivation and become a good mediator for students in improving discipline prayers and supported by the school's policy. Inhibiting factor in improving student discipline prayers is the environment where students hang out, infrastructure, social media technology that makes students forget to have the arrival time of prayer and so forth